2006
DOI: 10.1007/11767077_13
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Random Testing Through Iterative Partitioning

Abstract: Random Testing (RT) is an important and fundamental approach to testing computer software. Adaptive Random Testing (ART) has been proposed to improve the faultdetection capability of RT. ART employs the location information of successful test cases (those that have been executed but not revealed a failure) to enforce an even spread of random test cases across the input domain. Distance-based ART (D-ART) and Restriction-based ART (R-ART) are the first two ART methods, which have considerably improved the fault-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
1
30
0
3
Order By: Relevance
“…In this paper, we consider but one of the ART family of algorithms, namely, Iterative Partitioning ART (IP-ART) [6]. The original IP-ART algorithm works on the real domain, and we revised the algorithm so that it works on the integer domain.…”
Section: An Algorithm Of Generating Priority Numbersmentioning
confidence: 99%
“…In this paper, we consider but one of the ART family of algorithms, namely, Iterative Partitioning ART (IP-ART) [6]. The original IP-ART algorithm works on the real domain, and we revised the algorithm so that it works on the integer domain.…”
Section: An Algorithm Of Generating Priority Numbersmentioning
confidence: 99%
“…Therefore, Adaptive Random Testing has been proposed for common failure patterns in terms of test cases to detect the failure. However, in recent study [4] it has been found that the performance of a partition testing strategy depends not only on the failure rate, it also on the geometric pattern of the failure-causing inputs. The new type of random testing is developed as adaptive random testing which shows that the effectiveness of random testing also it can be improved without incurring significant overheads rather than ordinary random testing.…”
Section: Introductionmentioning
confidence: 99%
“…접근이 가장 용이한 소프트웨어 테스트 자동화 방법의 하나인 랜덤 테스팅은 입력 도메인 내에서 임의의 값을 선택 하여 테스트 케이스를 생성하고, 이를 이용하여 주어진 소프 트웨어에 대한 테스팅을 수행하도록 한다. 이와 같은 랜덤 테스팅은 소프트웨어 테스팅 자동화를 위한 가장 기본적이고 중요한 방법의 하나로 [7], 다양한 어플리케이션에 성공적으로 적용되어왔다 [9,11]. 하지만 랜덤 테스팅은 테스트되는 소프 트웨어에 대한 정보를 전혀 이용할 수 없다는 제약을 가지기 때문에, Chen 등은 소프트웨어 내의 오류들이 특정한 형태를 이루는 경우, 테스트 케이스를 입력 도메인 내에 넓고 고르 게 분산시켜 순수 랜덤 테스팅에서보다 더 효율적으로 오류 를 찾아낼 수 있도록 하는 적응적 랜덤 테스팅(Adaptive Random Testing, ART)을 제안했고, 이를 기반으로 하는 다 양한 응용 기법들이 제안되어 왔다.…”
unclassified
“…하지만 랜덤 테스팅은 테스트되는 소프 트웨어에 대한 정보를 전혀 이용할 수 없다는 제약을 가지기 때문에, Chen 등은 소프트웨어 내의 오류들이 특정한 형태를 이루는 경우, 테스트 케이스를 입력 도메인 내에 넓고 고르 게 분산시켜 순수 랜덤 테스팅에서보다 더 효율적으로 오류 를 찾아낼 수 있도록 하는 적응적 랜덤 테스팅(Adaptive Random Testing, ART)을 제안했고, 이를 기반으로 하는 다 양한 응용 기법들이 제안되어 왔다. [4,[6][7][8][9][10].…”
unclassified
See 1 more Smart Citation